Information security applications : 17th International Workshop, WISA 2016, Jeju Island, Korea, August 25-27, 2016, Revised selected papers /: 17th International Workshop, WISA 2016, Jeju Island, Korea, August 25-27, 2016, Revised selected papers. (2017) - Unknown
No abstract available